Integration of Kaliurang Local Culture into Augmented Reality for Spatial Geometry Learning Media Development - Rachman, Kufita; Rasyid, Ilham; Arbiyanti, Ade Puteri; Vesya, Siti Raihani (Wise Education, 2025)
A new challenge in 21st-century learning processes is the demand for technology integration without neglecting the richness of local culture. This research aims to develop Augmented Reality (AR) learning media integrated with the local culture of Kaliurang that is feasible and practical to use. This research approach uses a quantitative and qualitative approach, also known as a mixed method, with a research and development (R&D) design model 4-D consisting of four stages: define, design, develop, and disseminate. Data collection was conducted through interviews and questionnaires. The selection of subjects was carried out through random sampling with a population of sixth-grade students. The sample used in this study consisted of 25 sixth-grade students from SD Negeri Umbulharjo 2 over 2 months. The analysis of interview data was conducted descriptively, while the questionnaire data used descriptive statistical analysis. The analysis results found the need for the development of learning media, which was subsequently assessed for feasibility with an average score of 3.93 or 98.43%, categorized as